Teaching practices and perspectives regarding word counting units - Louis Lafleur (Vocabulary Learning and Instruction)
The selection of an appropriate word counting unit (WCU) for the purpose of second/foreign language vocabulary acquisition (SLVA) in the last decade has become a very important and relevant topic in academic circles. However, few studies address on-the-ground teaching practices and perspectives. This mixed-approach study, conducted through an online questionnaire, collected both quantitative and qualitative data from 30 ESL/EFL teachers in Japan. The questionnaire surveyed their vocabulary teaching experience and views regarding five categories of WCUs: all word tokens (i.e., All Forms and Meanings (AFM)), plemma, lemma, flemma, and Word Family (WF). The online survey revealed that most participants (i.e., those who were not aware of SLVA research and recent teaching practices) had limited experience and knowledge regarding WCUs and their impact. Another important finding is that although the WCU category participants were most experienced with is the WF (i.e., root/basic word lists), the WCU they have the highest pedagogical regard for is the lemma which considers parts of speech (POS) in vocabulary instruction and learning, followed closely by the plemma which additionally considers the various meanings words can take on, and also irregular inflectional patterns (e.g., irregular verb past tenses and past participles), and to a lesser extent the flemma which does not consider POS nor the various meanings and irregular inflectional patterns of words in vocabulary instruction.